Health Risks and Opportunities for Harm Reduction Among Injection-drug-using Clients of Saskatoon’s Needle Exchange Program - Laurie, Maureen L. (Can J Public Health, 2000)
Information about injection drug users’ lifestyles is necessary to develop effective harm reduction strategies. One way to gather this information is through needle exchange programs. In 1998, a convenience sample of 100 clients of Saskatoon’s needle exchange service was interviewed about their injection and sexual practices. Ritalin and morphine were the most commonly injected drugs. Over half the participants (53%) reported having shared needles, usually with friends, relatives, and partners. Slightly more (62%) had shared injection equipment. Most participants had multiple sexual partners, especially the women, half of whom were sex trade workers. Condom use was higher with casual partners than with regular partners. While awareness about HIV transmission was high, most participants considered their risk of infection to be below average. These findings are discussed in light of the insights they provide regarding both health risks and opportunities for harm reduction in the study population.